PENGARUH LAMA PENDAMPINGAN TENTANG SANITASI DAN HIGIEN TERHADAP TOTAL BAKTERI PADA AIR PENCUCI WARUNG MAKAN DI SEKITAR UNIMUS - Nurrahman . .; Setyaningrum . . (JURNAL LITBANG, 2005)
Abstract Water is very important in human live for food processing such as in restaurant, but it has effects by health. Water is carrying some of pathogenic bacteria that effect by health. This experiment was carry out with effect of long time of accompany about sanitation and hygiene on total bacteria in restaurant washing water around of UNIMUS. The Research result was long time of accompanies about sanitation and hygiene had effect on total of bacteria. Increasing of long time of accompany to decrease total of bacteria. Keywords: water long tine of accompany, sanitation and hygiene and restaurant